Appropriate Self-Perceived Behaviors in Primary Education Pupils During Sports Games - Gil-Madrona, Pedro; Gómez, José Luis; Aguilar-Jurado, Miguel Ángel; Gutiérrez-Marín, Eva Cristina (Frontiers in Psychology, 2020)
Based on the results obtained from primary education students—fifth and sixth graders—the aim of this work is to check the appropriate self-perceived behaviors during and at the end of the game. The study population was made up of 698 students from fifth and sixth grade in the Autonomous Region of Castilla–La Mancha (Spain). Data were collected through a questionnaire (scale) on the social skills of primary school students linked to the adequate skills when losing, the adequate skills when winning, and the adequate skills during the game. Study results revealed that analyzed behaviors vary, depending on the moment of the game, being it more frequently during the development of the game than when losing or winning.